The Prognostic Significance of Metastatic Nodal Size in Non-surgical Patients With Esophageal Squamous Cell Carcinoma - Zhao, Zongxing; Zhang, Yanan; Wang, Xin; Wang, Peiliang; Geng, Xiaotao; Zhu, Liqiong; Li, Minghuan (Frontiers in Oncology, 2020)
Background: The present study aimed to determine the prognostic value of the size of metastatic lymph node (LN) in non-surgical patients with esophageal squamous cell carcinoma (ESCC). Methods: Three hundred seventy-six ESCC patients treated with definitive (chemo-) radiotherapy from January 2013 to March 2016 were reviewed. We analyzed potential associations of metastatic nodal size with responses, patterns of failure, and survival. Log-rank testing and Cox proportional hazards regression models were used to assess the impact of the clinical factors on survival. Results: The 3-years over survival (OS) rates following a median follow-up of 28.2 months were 53.2, 46.2, 35.5, and 22.7% for the N0 group, the >0.5 to ≤1 cm group, the >1 to ≤2 cm group, and the >2 cm group, respectively. The progression-free survival (PFS) rates for 2 years were 50.9, 44.2, 26.6, and 23.4% for the N0 group, the >0.5 to ≤1 cm group, the >1 to ≤2 cm group, and the >2 cm group, respectively. The objective response rates (ORR) for the 280 patients with metastatic LNs were 43.1% for the LN >0.5 to ≤1 cm group, 46.9% for the LN >1 to ≤2 cm group, and 25.5% for the LN ≥2 cm group. The LN >2 cm group had the worst ORR of the three groups with LNs. Gross tumor volume (GTV) failure was the most common failure pattern, followed by distant failure and out of GTV LN failure, with incidences of 47.9% (180 of 376), 42% (158 of 376), and 13.8% (52 of 376), respectively. Nodal size correlated statistically with GTV failure and distant failure but not with out-of-GTV nodal failure. After adjusting for age, sex, T category, Primary tumor location, and CRT, the size of metastatic LNs was an independent prognostic factor for OS and PFS in multivariate analyses. Conclusions: Nodal size is one of prognostic factors for non-surgical patients with ESCC and correlated statistically with GTV failure and distant failure.